KONDISI FISIK RUMAH DAN PERILAKU MEMBUANG SAMPAH DI PEMUKIMAN NELAYAN CUMPAT KECAMATAN BULAK KOTA SURABAYA TAHUN 2022 - Clara Intan Pratiwi; Imam Thohari; Pratiwi Hermiyanti; Narwati; Putri Arida Ipmawati (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Surabaya, 2022)
A healthy house can be assessed from the physical condition of the house and behavior in disposing of waste. The coverage of healthy homes in Kedung Cowek Village in 2019 was 26%, in 2020 and 2021 it was 27%. The Cumpat Fisherman Settlement Community has the behavior of throwing garbage in the sea because of the irregular transportation system. The purpose of this study was to analyze descriptively the physical condition of the house and the behavior of disposing of garbage in the Cumpat Fisherman's Settlement, Bulak District, Surabaya City. This research uses descriptive method, the sample size is 84 houses and 83 respondents using Proportionate Stratified Random Sampling. Collecting data using observation sheets and questionnaire sheets. The results of the study were analyzed and presented through a frequency distribution table. The results of the study on the physical condition of the house met the requirements of a healthy house (97.6%) by reviewing the ceiling, walls, floor, lighting, ventilation, temperature, humidity, and occupancy density. The results of the study regarding the behavior of disposing of waste were in good category (83.3%) but the action component was in the sufficient category (16.7%). The conclusion of the study on the assessment of the physical condition of the house obtained results that met the requirements and the behavior of disposing of garbage obtained a good category. It is necessary to hold outreach on the impact of disposing of waste on marine ecosystems and healthy homes, training on recycling, and making banners containing the prohibition of throwing garbage.